The decoupling between gas exchange and water potential of Cinnamomum camphora seedlings during drought recovery and its relation to ABA accumulation in leaves. (26th August 2020) - Duan, Honglang; Wang, Defu; Wei, Xiaohua; Huang, Guomin; Fan, Houbao; Zhou, Shuangxi; Wu, Jianping; Liu, Wenfei; Tissue, David T; Wan, Songze
Abstract: Aims: Drought stress and the degree of drought severity are predicted to rise under highly variable patterns of precipitation due to climate change, while the capacity of trees to cope with drought recovery through physiological and biochemical adjustment remains unclear. We aimed to examine the coupling of physiology and biochemistry in trees during drought and the following recovery. Methods: Potted seedlings of Cinnamomum camphora were grown under well watered conditions prior to the experimental drought stress, which was initiated by withholding water. Seedlings were rewatered following attainment of two drought severities: mild drought (stomatal closure) and moderate drought ( ψ xylem = −1.5 MPa). We measured leaf-level water potential, gas exchange (photosynthesis and stomatal conductance), abscisic acid (ABA), proline and non-structural carbohydrates (NSCs) concentrations in seedlings of C. camphora during drought and a 4-day recovery. Important Findings: We found that drought severity largely determined physiological and biochemical responses and affected the rate of recovery. Stomatal closure occurred at the mild drought stress, accompanied with ABA accumulation in leaves and decline in water potential, while leaf proline accumulation and variable NSC were evident at the moderate drought stress. More severe drought stress led to delayed recovery of gas exchange, but it did not have significant effect on water potential recovery. The relationships of water potential and gas exchange differed during drought stress and post-drought recovery. There was tight coupling between water potential and gas exchange during drought, but not during rewatering due to high ABA accumulation in leaves, thereby delaying recovery of stomatal conductance. Our results demonstrate that ABA could be an important factor in delaying the recovery of stomatal conductance following rewatering and after water potential recovery of C. camphora . Furthermore, greater drought severity had significant impacts on the rate of recovery of tree physiology and biochemistry. Graphical Abstract: